2018
DOI: 10.1002/ece3.4679
|View full text |Cite
|
Sign up to set email alerts
|

Responses of macroalgae to CO2 enrichment cannot be inferred solely from their inorganic carbon uptake strategy

Abstract: Increased plant biomass is observed in terrestrial systems due to rising levels of atmospheric CO2, but responses of marine macroalgae to CO2 enrichment are unclear. The 200% increase in CO2 by 2100 is predicted to enhance the productivity of fleshy macroalgae that acquire inorganic carbon solely as CO2 (non‐carbon dioxide‐concentrating mechanism [CCM] species—i.e., species without a carbon dioxide‐concentrating mechanism), whereas those that additionally uptake bicarbonate (CCM species) are predicted to respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 108 publications
2
31
0
Order By: Relevance
“…On the other hand, the net photosynthetic rate and chlorophyll content were reduced under the high pCO 2 levels. Similar results have been shown for Alaria esculenta (Gordillo et al, 2015) and Lomentaria australis (Van der Loos, Schmid & Leal, 2019). Elevated pCO 2 could accelerate the degradation of chlorophyll synthesis immoderately, which is not essential for light harvesting (Gordillo et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the net photosynthetic rate and chlorophyll content were reduced under the high pCO 2 levels. Similar results have been shown for Alaria esculenta (Gordillo et al, 2015) and Lomentaria australis (Van der Loos, Schmid & Leal, 2019). Elevated pCO 2 could accelerate the degradation of chlorophyll synthesis immoderately, which is not essential for light harvesting (Gordillo et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…The decrease in δ 13 C values detected in the future scenario relative to the current scenario at the final sampling indicates a down‐regulation of the CCM. This can provide energetic savings in seaweeds, as the use of CO 2 as an inorganic carbon source requires less energy than HCO3- (Cornwall et al, 2017; van der Loos et al, 2019). Any saved energy was not invested in growth (in contrast to that reported for a red seaweed by van der Loos et al, 2019), but instead could have been invested in the adjustment of fatty acid composition in response to elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that nitrogen incorporation during the day is energetically less expensive than at night. This is because during daylight, the energy and carbon necessary for the assimilation process are provided directly by photosynthesis; whereas, in the dark, accumulated carbohydrates are the energy source (Huppe & Turpin 1994;Turpin 1991). Several studies have revealed higher daytime uptake rates of NH 4 + and NO 3 − compared to nighttime.…”
Section: Lightmentioning
confidence: 99%